Papel do receptor de PAF na infecção experimental pelo vírus influenza A - Cristiana Couto Garcia (2009)
Flu is a respiratory illness of great global relevance, as it causes large number of hospitalizations and deaths during epidemics and pandemics. Strategies to combat the Influenza virus face challenges such as the emergence of strains resistant to vaccines and antiviral drugs. It is known that exacerbated inflammatory responses to the virus are causes of morbidity associated with infection. The Platelet Activation Factor PAF is a phospholipid mediator with direct effects on inflammatory responses such as leukocyte activation and transmigration. This study evaluated the role of PAF receptor during infection by H1N1 and H3N1 influenza virus subtypes. To this purpose, a murine model of infection was determined with two inocula of H1N1 virus, 104 and 106 PFU and the inoculum of 106 PFU of the virus H3N1. PAFR KO and WT mice were infected by the two subtypes of virus and had weight loss and lethality monitored for 21 days. Animals infected with H1N1 virus were sacrificed at 5 or 8 days of infection to verify the recruitment and leukocyte activation, production of cytokines and chemokines, viral load, cell survival and tissue injury. The PAF receptor antagonist, PCA 4248, was also used during H1N1 virus infection and evaluation of lethality, weight loss and inflammatory parameters. The results showed that the development of the signs associated with the disease is progressive and dependent on the inoculum and viral strain used. The H1N1 virus, more pathogenic, caused an intense neutrophilic infiltrate into the airways and lungs, pulmonary edema, tissue injury and high production of proinflammatory cytokines. PAFR KO animals were protected from lethality and weight loss caused by H1N1 and H3N1 viruses compared to WT. The PAFR antagonist PCA provided similar protection to the PAFR KO mice against H1N1 infection. The protection was related to the reduction in neutrophils recruitment to the airways, in protein leakage and lung damage. There was also an increase in NK and NKT cells, but lower production of cytokines related to activation of the same, less deactivation of phagocytes, higher levels of apoptosis in the lungs, similar or greater viral clearance. The absence of PAFR kept the adaptive response to reinfection. Thus we conclude that PAFR has a crucial role in the pathogenesis of influenza and may represent a therapeutic target to control inflammation associated with infection.